2016
DOI: 10.1074/jbc.m116.742163
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Interactions Between Contactin Family Members and Protein-tyrosine Phosphatase Receptor Type G in Neural Tissues

Abstract: Protein-tyrosine phosphatase receptor type G (RPTP␥/ PTPRG) interacts in vitro with contactin-3-6 (CNTN3-6), a group of glycophosphatidylinositol-anchored cell adhesion molecules involved in the wiring of the nervous system. In addition to PTPRG, CNTNs associate with multiple transmembrane proteins and signal inside the cell via cis-binding partners to alleviate the absence of an intracellular region. Here, we use comprehensive biochemical and structural analyses to demonstrate that PTPRG⅐CNTN3-6 complexes sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 62 publications
2
49
0
Order By: Relevance
“…3E-G). To understand the structure of entire extracellular domain, the domains of lg5 -lg6 and FNIII1 -FNIII2 were docked by the homology model of CNTN3 Ig5 -FNIII_2 fragment (PDBID: 5I99; 45.3% identity to the corresponding domains in human CNTN2), while the domain FNIII3 -FNIII4 were docked by the homology model of mouse CNTN2 FNIII_1 -FNIII_3 (PDBID: 5E7L) in each IPET 3D density maps 15 . Similar docking studies in the IPET maps of Category 2 particles revealed a fundamentally different arrangement with the first four Ig domains in an extended conformation resembling beads-on-a-string ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…3E-G). To understand the structure of entire extracellular domain, the domains of lg5 -lg6 and FNIII1 -FNIII2 were docked by the homology model of CNTN3 Ig5 -FNIII_2 fragment (PDBID: 5I99; 45.3% identity to the corresponding domains in human CNTN2), while the domain FNIII3 -FNIII4 were docked by the homology model of mouse CNTN2 FNIII_1 -FNIII_3 (PDBID: 5E7L) in each IPET 3D density maps 15 . Similar docking studies in the IPET maps of Category 2 particles revealed a fundamentally different arrangement with the first four Ig domains in an extended conformation resembling beads-on-a-string ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To date, all of the crystal structures of the Ig1-Ig4 headpiece in CNTNs and related proteins have revealed a compact horseshoe-shaped configuration [12][13][14][15][16][17][18][19][20][21] . However, the data presented here reveal that most of the CNTN2 particles in our EM images in fact do not adopt a closed horseshoe-shaped Ig1-Ig4 headpiece.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations